14-3-3 Regulates Actin Filament Formation in the Deep-Branching Eukaryote Giardia lamblia - Jana Krtková (American Society for Microbiology, 2017)
ABSTRACT The phosphoserine/phosphothreonine-binding protein 14-3-3 is known to regulate actin; this function has been previously attributed to sequestration of phosphorylated cofilin. 14-3-3 was identified as an actin-associated protein in the deep-branching eukaryote Giardia lamblia; however, Giardia lacks cofilin and all other canonical actin-binding proteins (ABPs). Thus, the role of G. lamblia 14-3-3 (Gl-14-3-3) in actin regulation was unknown. Gl-14-3-3 depletion resulted in an overall disruption of actin organization characterized by ectopically distributed short actin filaments. Using phosphatase and kinase inhibitors, we demonstrated that actin phosphorylation correlated with destabilization of the actin network and increased complex formation with 14-3-3, while blocking actin phosphorylation stabilized actin filaments and attenuated complex formation. Giardia’s sole Rho family GTPase, Gl-Rac, modulates Gl-14-3-3’s association with actin, providing the first connection between Gl-Rac and the actin cytoskeleton in Giardia. Giardia actin (Gl-actin) contains two putative 14-3-3 binding motifs, one of which (S330) is conserved in mammalian actin. Mutation of these sites reduced, but did not completely disrupt, the association with 14-3-3. Native gels and overlay assays indicate that intermediate proteins are required to support complex formation between 14-3-3 and actin. Overall, our results support a role for 14-3-3 as a regulator of actin; however, the presence of multiple 14-3-3–actin complexes suggests a more complex regulatory relationship than might be expected for a minimalistic parasite. IMPORTANCE Giardia lacks canonical actin-binding proteins. Gl-14-3-3 was identified as an actin interactor, but the significance of this interaction was unknown. Loss of Gl-14-3-3 results in ectopic short actin filaments, indicating that Gl-14-3-3 is an important regulator of the actin cytoskeleton in Giardia. Drug studies indicate that Gl-14-3-3 complex formation is in part phospho-regulated. We demonstrate that complex formation is downstream of Giardia’s sole Rho family GTPase, Gl-Rac. This result provides the first mechanistic connection between Gl-Rac and Gl-actin in Giardia. Native gels and overlay assays indicate intermediate proteins are required to support the interaction between Gl-14-3-3 and Gl-actin, suggesting that Gl-14-3-3 is regulating multiple Gl-actin complexes.